Physiological and Clinical Aspects of Bioactive Peptides from Marine Animals - Sukwasa Chakniramol; Andreas Wierschem; Man-Gi Cho; Khawaja Muhammad Imran Bashir (MDPI AG, 2022)
Biological molecules in nutraceuticals and functional foods have proven physiological properties to treat human chronic diseases. These molecules contribute to applications in the food and pharmaceutical industries by preventing food spoilage and cellular injury. Technological advancement in the screening and characterization of bioactive peptides has enabled scientists to understand the associated molecules. Consistent collaboration among nutritionists, pharmacists, food scientists, and bioengineers to find new bioactive compounds with higher therapeutic potential against nutrition-related diseases highlights the potential of the bioactive peptides for food and pharmaceutic industries. Among the popular dietary supplements, marine animals have always been considered imperative due to their rich nutritional values and byproduct use in the food and pharmaceutical industries. The bioactive peptides isolated from marine animals are well-known for their higher bioactivities against human diseases. The physiological properties of fish-based hydrolyzed proteins and peptides have been claimed through in vitro, in vivo, and clinical trials. However, systematic study on the physiological and clinical significance of these bioactive peptides is scarce. In this review, we not only discuss the physiological and clinical significance of antioxidant and anticancer peptides derived from marine animals, but we also compare their biological activities through existing in vitro and in vivo studies.